Learning Curve for Laparoscopic Repair of Pediatric Inguinal Hernia Using Percutaneous Internal Ring Suturing - Zenon Pogorelić; Dario Huskić; Tin Čohadžić; Miro Jukić; Tomislav Šušnjar (MDPI AG, 2021)
Background: Percutaneous internal ring suturing (PIRS) is a simple and popular technique for the treatment of inguinal hernia in children. The aim of this study was to analyze the learning curves during implementation of PIRS in our department. Methods: A total of 318 pediatric patients underwent hernia repair using the PIRS technique by three pediatric surgeons with different levels of experience in laparoscopic surgery. These patients were enrolled in a prospective cohort study during the period October 2015-January 2021. Surgical times, intraoperative and postoperative complications, in addition to outcomes of treatment were compared among the pediatric surgeons. Results: Regarding operative time a significant difference among the surgeons was found. Operative time significantly decreased after 25-30 procedures per surgeon. The surgeon with advanced experience in laparoscopic surgery had significantly less operative times for both unilateral (12 (interquartile range, IQR 10.5, 16.5) min vs. 21 (IQR 16.5, 28) min and 25 (IQR 21.5, 30) min; p = 0.002) and bilateral (19 (IQR 14, 21) min vs. 28 (IQR 25, 33) min and 31 (IQR 24, 36) min; p = 0.0001) hernia repair, compared to the other two surgeons. Perioperative complications, conversion, and ipsilateral recurrence rates were higher at the beginning, reaching the benchmarks when each surgeon performed at least 30 PIRS procedures. The most experienced surgeon had the lowest number of complications (1.4%) and needed a fewer number of cases to reach the plateau. The other two surgeons with less experience in laparoscopic surgery had higher rates of complications (4.4% and 5.4%) and needed a higher number of cases to reach the plateau (p = 0.190). Conclusions: A PIRS learning curve for perioperative and postoperative complications, recurrences, and conversion rates reached the plateau after each surgeon had performed at least 30 cases. After that number of cases PIRS is a safe and effective approach for pediatric hernia repair. A surgeon with an advanced level of experience in pediatric laparoscopic surgery adopted the technique more easily and had a significantly faster learning curve.